Watershed: a more efficient sampling unit for mountain camera traps - Jun-Jie Li; Yi-Hao Fang; Ji-Cong Zhan; Xue-Jun Yang; Can-Bin Huang; Yan-Peng Li; Kun Tan; Zhi-Pang Huang; Liang-Wei Cui; Wen Xiao (Scientific Reports)
Abstract Wildlife camera trap (CT) surveys typically employ two-dimensional equal-area grid sampling, which often neglects the influence of complex mountainous terrain on species distribution, potentially yielding misleading outcomes. A watershed, incorporating diverse habitats from high to low elevations and from rivers to ridges, aligns with complex mountains. Monitoring based on watersheds might address this. In southwest China’s mountain forests, under comparable sampling intensities, we contrasted the capture rate (CR), species richness, and relative abundance index (RAI) of dominant species among watershed, 1 × 1 km² grid, and elevation gradient patterns. Also, habitat factor correlations and heterogeneities were analyzed. Results reveal higher CR, species richness, and habitat heterogeneity in the watershed pattern. The elevation gradient pattern shows more stable species and RAI than the grid pattern. In small-scale mountains, topographic factors indirectly affect CT survey results via vegetation distribution. Analysis of similarities (ANOSIM) indicates significant differences in species and community among watersheds. Using watersheds as sampling units for CTs can match the mountains’ elevation differences and complex topography well, aids in capturing wildlife diversity and understanding mountain species distribution. Therefore, we recommend that the spatial sample design in mountainous areas should be based on watersheds, taking elevation gradients and topography into consideration.